PENERAPAN ASAS NE BIS IN IDEM DALAM HUKUM PIDANA INTERNASIONAL - Putri Saraswati, Made; Oka Parwata, A. A. Gede (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 03, Mei 2014)
Ne bis in idem principle is very important to protect individuals not to be punished more than once for the same offence. However,international practice shows that the application of this principle can be ruled out if the crime has linkage jurisdiction between two or more countries. Similarly, the International Criminal Court (ICC) can also override this principle and has the authority to prosecute or try a repetitive justice to the perpetrators of serious human rights crimes in the territory of contracting parties of the Rome Statute. This article discusses that the override of this principle may affect the jurisdiction of a country and directly “intimidates" its legal sovereignty.
Keywords: Ne bis in idem, serious human rights crimes, State sovereignty